2010
DOI: 10.1136/tc.2009.030692
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between ad volume and awareness of a tobacco education media campaign

Abstract: BackgroundThe relation between aided ad recall and level of television ad placement in a public health setting is not well established. We examine this association by looking back at 8 years of the California's Tobacco Control Program's (CTCP) media campaign.MethodsStarting in July 2001, California's campaign was continuously monitored using five telephone series of surveys and six web-based series of surveys immediately following a media flight. We used population-based statewide surveys to measure aided reca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Although higher expenditures and subsequently higher volumes of advertisement exposure are recalled more often (47) and associated with higher levels of quitting behavior and lower smoking prevalence (39,57), our findings appear to indicate that the quality of the advertisement also matters. If CTCP's only interest were cessation, CTCP could have saved an additional $##, had they only implemented "Stages" rather than all four advertisements, while reaching the same demographic groups and conferring the same effects on cessation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although higher expenditures and subsequently higher volumes of advertisement exposure are recalled more often (47) and associated with higher levels of quitting behavior and lower smoking prevalence (39,57), our findings appear to indicate that the quality of the advertisement also matters. If CTCP's only interest were cessation, CTCP could have saved an additional $##, had they only implemented "Stages" rather than all four advertisements, while reaching the same demographic groups and conferring the same effects on cessation.…”
Section: Discussionmentioning
confidence: 58%
“…The higher reported recall of this advertisement may be partially explained by the rating points of this advertisement (47). The advertisement was aired more frequently than two of the others and therefore might have had a better chance of being seen.…”
Section: Discussionmentioning
confidence: 93%
“…These campaigns have included cessation-focused and general anti-smoking messages 76 77. They are considered effective in motivating smokers to quit and in changing social norms on smoking 71 78…”
Section: Population Cessation: Interventions Consideredmentioning
confidence: 99%
“…He reported that in ‘preliminary analyses’, cumulative Gross Rating Points (GRPs) had stronger relationships with both aided ad recall and confirmed ad recall than GRPs from the most recent flight (3–6 months before the survey was administered) 10. This relationship was confirmed by Cowling et al 11 when he compared cumulative i TRPs to flight TRPs and TRP density with aided ad recall and found the strongest relationship was with cumulative TRPs.…”
Section: Introductionmentioning
confidence: 91%
“…The first approach shows participants a full-length video of the ad before assessing awareness, such as in the evaluation of the Tips From Former Smokers campaign 17. The second approach presents a single screenshot from the ad, such as in the CDPH's studies 11. Despite substantial differences in methodologies, awareness rates are compared with each other without acknowledgement of the different approaches, and an ad campaign may be deemed a success or failure based on such comparisons.…”
Section: Introductionmentioning
confidence: 99%